"You Gotta Admit You Had It Comin to You": Trauma, Gender Violence and Female Bonding in Marsha Norman’s Getting Out - Maika Aira Gallardo (Miscelánea: A Journal of English and American Studies, 2016)
During the 1970s, and especially during the 1980s and 1990s, gender violence began to receive the attention of literary theorists, who explored it from a variety of different perspectives. One such approach was Trauma Studies theory, which, from the 1990s onwards, established gender violence as the third significant site of psychological trauma, along with hysteria and shell-shock postwar trauma, and tried to explain the origins of gender violence using historical, sociological and psychological evidence. In this essay, I will adopt the theoretical basis provided by trauma studies to analyze a case of post-traumatic stress disorder presented on stage: the character of Arlene-Arlie in Marsha Norman’s play Getting Out (1978). This work offers an example of how the devastating effects of trauma transform a person to the extent of causing in her an identity crisis which forces her to remain on constant alert against anyone who tries to get close to her.